The IVP women's Bible commentary - Kroeger, Catherine Clark; Evans, Mary J. (Downers Grove, Ill. : InterVarsity Press, 2002)
This commentary searches Scripture in light of the many theological, biblical, sociological and psychological concerns of women. Led by editors Catherine Clark Kroeger and Mary J. Evans, an international team of contributors offers thoughtful, engaging insight to complement more traditional approaches that have viewed Scripture primarily through the experiences and understanding of men. The IVP women's bible commentary shows how relevant Scripture is to the legitimate concerns of men and women alike--and just how transforming God's Word can be when viewed from unaccustomed perspective.
Includes bibliographical references and indexes.
Keywords: Bible -- Feminist criticism